Analysis of the Phenomenon of Papuan Armed Criminal Conflict Against Indonesian Sovereignty - Zammara, Aurel Meidina; Darmawan, Abqary Faraz; Kumoro, M Damar Setyo; Sambarana, Ilyasa Laits; Damareka, M Darrell; Aulia, Padla Zan Putri; Amalia, Firda; S, Debby Nauly Rafeyfa; Veronica, Ester; W, Yuliana Yuli; Suprima, Suprima; Mulyadi, Mulyadi; Maulinda, Rerin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This article discusses the phenomenon of Armed Criminal Groups (KKB) in Papua and the influence of their existence on the sovereignty of the Indonesian state. The background of this research is based on curiosity about the impact of the Papuan KKB on state sovereignty. The purpose of this study is to find out whether the existence of the Papuan KKB affects the sovereignty of the Unitary State of the Republic of Indonesia and how steps can be taken to resolve this problem. The research method used is a quantitative approach, where data is collected using questionnaires that are distributed to resource persons and then the results are analyzed through questionnaire diagrams. This study aims to provide a clear and objective picture of the current situation and how it impacts the country's sovereignty. The results showed that the phenomenon of the Papuan KKB had an impact that threatened the sovereignty of the Unitary State of the Republic of Indonesia. These findings demonstrate the importance of taking this issue seriously and strategically by the Indonesian government. This research is expected to be a reference in decision making and policy formulation related to the issue of Papuan KKB.